THE EFFECT OF BRAND IMAGE AND BRAND TRUST ON THE PURCHASE DECISION OF COFFEE OF PROMISE OF SOULS ON MANAGEMENT STUDENTS OF UBP KARAWANG - Nicky Amanda Indriyani; Citra Savitri; Wike Pratiwi (Jurnal Ekonomi, 2022)
This study aims to determine the effect of brand image and trademark trust on purchasing decisions on Coffee Janji Jiwa (Case Study: Management Students at Buana Perjuangan University). This research was conducted by quantitative descriptive methods, the variables in this study were 2 independent variables (X), namely brand image and brand trust and dependent variable (Y), namely the purchasing decisions measured using primary data from the questionnaire. The population in this study was the Management Student of the University of Buana Perjuangan Karawang with a sample calculation using the Slovin formula consisting of 101 respondents. The data analysis technique used is the validity test, reliability test, multiple linear analysis, t test and F test using the IBM Statistics SPSS 22 program. The results showed that there was a positive and significant effect of the brand image on the purchasing decision on the Kopi Janji Jiwa with T value of 2,268 > t Table 1.987. There was a positive and significant effect of the brand trust on the purchasing decision on the Kopi Janji Jiwa with T value of 3,249 > t Table 1.987